Analysis of the Development of Zakat Accounting Research: A Bibliometric Approach - Anastasya Dinda Syaputri Anas; Sigid Eko Pramono Sigid (Newinera Publisher, 2024)
This study addresses the scarcity of bibliometric research in zakat accounting literature by qualitatively analyzing 321 articles from the Dimension AI database spanning 1994 to 2023. The study has found the Journal of Islamic Economics and Theory as a journal that is very relevant and has a significant impact, besides the Journal of Islamic Accounting and Business Research and the Journal of Islamic and Middle Eastern Finance and Management. The study also found several well-known writers, including Ahmad Kudhori and Hedi Pandowo, as well as influential figures such as Abu Bakar. Key themes encompass Financial Statements, PSAK, and Analysis, with 2023 trends focusing on information, accountability, quality research, and impact in zakat accounting. The study foresees ongoing significance of accountability and accounting information in 2023. Employing bibliometric analysis, the research facilitates the identification of zakat accounting issues, enhancing economic efficiency, and guiding researchers in prioritizing topics based on prevailing trends. This comprehensive overview contributes significantly to the evolving landscape of zakat accounting literature.